Biosynthesis of heme O in intraerythrocytic stages of Plasmodium falciparum and potential inhibitors of this pathway - Simão Gurge, Raquel M. (2019)
A number of antimalarial drugs interfere with the electron transport chain and heme-related reactions; however, the biosynthesis of heme derivatives in Plasmodium parasites has not been fully elucidated. Here, we characterized the steps that lead to the farnesylation of heme. After the identification of a gene encoding heme O synthase, we identified heme O synthesis in blood stage parasites through the incorporation of radioactive precursors. The presence of heme O synthesis in intraerythrocytic stages of Plasmodium falciparum was confirmed by mass spectrometry. Inabenfide and uniconazole–P appeared to interfere in heme synthesis, accordingly, parasite growth was also affected by the addition of these drugs. We conclude that heme O synthesis occurs in blood stage-P. falciparum and this pathway could be a potential target for antimalarial drugs.